Contact Lenses and Infectious Keratitis: From a Case-Control Study to a Computation of the Risk for Wearers. Issue 6 (June 2020) - Sauer, Arnaud; Greth, Mathieu; Letsch, Jonathan; Becmeur, Pierre-Henri; Borderie, Vincent; Daien, Vincent; Bron, Alain; Creuzot-Garcher, Catherine; Kodjikian, Laurent; Burillon, Carole; Robert, Pierre-Yves; Mouriaux, Frédéric; et al.
Abstract : Purpose: Contact lens (CL)-related microbial keratitis (MK) has major public health implications, with about 300 million wearers worldwide, and certain potentially modifiable risk factors. This study aimed to identify the risk factors of CL-related MK. Methods: A multicenter case-control study was conducted between 2014 and 2017. Cases presenting with CL-related MK were submitted to an anonymous 52-item questionnaire, which was also completed by healthy controls. Univariate followed by multivariate logistic regression analysis was performed. Risk factors for CL-related MK were given as odds ratio (OR) with 95% confidence interval and P -value. Results: The study included a total of 2267 patients (1198 cases and 1069 controls). The MK risk factors for the daily disposable lenses group were exceeding the lens renewal period (OR = 9.16, P = 0.008) and occasionally wearing CL when sleeping (OR = 15.83, P = 0.035). The most important risk factors in the nondaily disposable lenses group were lens cleaning solution distributed by eye care brands (OR = 3.50, P < 0.001) and failure to renew lens cases (OR = 3.39, P = 0.001). Statistically and clinically significant variables were used to establish the MK risk equation for CL wearers, allowing an individual calculation of the risk of MK under lenses. Conclusions: The MK risk equation is a valuable tool for educating patients about the risks associated with wearing CL. It allows the patient to be informed about their overall risk of infection while detailing the precipitating elements of the infectious risk with the aim of modifying risk behavior. Abstract : Supplemental Digital Content is Available in the Text.